Vivência de adolescentes com diabetes mellitus tipo 1 na perspectiva da ética da alteridade - Cruz, Déa Silvia Moura da (2017)
Introduction: The adolescent with diabetes experiences the conflicts of adolescence and tackles the demands resulting from the disease and the medical therapy. Objective: To know the experience of adolescents with type 1 diabetes mellitus from the perspective of the Ethics of Otherness. Method: This is a qualitative and exploratory-descriptive study, which was performed in the Pediatric Outpatient Clinic of the Lauro Wanderley University Hospital, in the city of João Pessoa, with nine adolescents with type 1 diabetes. Data were collected by means of a focus group and semi-structured interviews, and were interpreted through thematic analysis. The study was approved by a Research Ethics Committee, protocol nº 1.203.218, CAAE 47909515.3.0000.5183. Results: The analysis of the speeches enabled us to build following categories: Living with diabetes; Experiences of adolescents with diabetes in the family environment; Experiences of adolescents with diabetes in the social environment and Experiences of adolescents with diabetes with the multidisciplinary team. Since the diagnosis, parents took the responsibility of caring for their children, and, from the perspective of the Ethics of Otherness, they were present and open to welcoming them as “Other”, thus supporting them in the medical therapy. The adolescents proved to be confident people, with preserved self-esteem, who manage to live in community, taking up their condition before their peers, thus becoming sensitive to their needs, making themselves present, helping them in self-care, as well as respecting them in their Otherness. The assistance received from the multidisciplinary team was considered by the adolescents as “optimal”, because the established relationship is pervaded by empathy, respect and complicity, although some ineffective strategies have been used by one of the team members, which did not contribute to changing the perception and behavior of the adolescent. Final Considerations: The adolescents with diabetes and their families are active subjects in the medical therapy and show peculiarities that need to be addressed in the therapeutic project. By knowing these experiences, from the perspective of the Ethics of Otherness, the multidisciplinary team may reflect on the care provided, thus respecting the otherness of the adolescents with diabetes, through a qualified listening to meet their peculiar demands.